Desenvolvimento de um espectrofotômetro para medidas de absorção/emissão na região do visível utilizando mini lâmpada incandescente, mídia de DVD e smartphone - Oliveira, Helton Jader Souza de (2015)
A spectrophotometer for absorption measurements / emission, simple, portable and as partially partial dual mode for quantitative experiments was constructed using cheap and available materials is proposed in this paper. The instrument, here called SpectroPhone consists of modules made of MDF, one DVD as a diffraction grating media, two mini white incandescent lamps as radiation source and a Smartphone to acquire images and perform data processing, such as detector. The pixels of a region produced in a spectral images provide qualitative and quantitative information after the application of the concepts and HSV color model RGB, respectively. A simple algorithm based on HSV was developed for the conversion of the hue values (H) in their corresponding λ. Its analytical performance was assessed by quantitative analysis based on analytical curves, specimens of which have been validated by analysis of variance (ANOVA). The SpectroPhone was applied to the determination of Fe2+ in the absorption mode in pharmaceutical samples, and Na+, in emission mode and in natural saline water. For comparison purposes, a commercial spectrophotometer for absorption mode and a photometer for commercial flame emission mode were used to construct the calibration curves of the reference instrument. Applying the paired t test at 95% confidence for the results of concentrations obtained with the instruments, it is observed that there was no statistically significant difference showing high precision and accuracy. SpectroPhone can be considered a good alternative to instrumental spectrometric measurements, not just limited to educational and academic purposes.